Aspirate sonorants and word-stress in Bhojpuri - Thakur, Gopal (Journal of Nepalese Studies, 2024)
Bhojpuri is a new Indo-Aryan language in South Asia. It is mainly spoken as a crossborder language between Nepal and India and written widely in Devanagari script. Phonemically, Bhojpuri has contrasts on the basis of aspiration, voice and breathiness. Besides these, Tiwari (1960/1984) and Shukla (1981) among others have recorded breathy sonorants against retroflex, nasal, flap and lateral model sonorant consonant phonemes in Bhojpuri. But they have presented them as a joint cluster of phonemic pairs in Devanagari script as presented in Hindi, Nepali, Maithili and some other Indo-Aryan languages to some extent. Similarly, word-stress is considered allophonic in Indo-Aryan languages, as Shukla (1981) has mentioned with Bhojpuri. But listening to such sonorant consonants, they don't seem so. Whatsoever, the phenomena were not examined empirically. So, this article includes empirical verification of the problem. To meet the objectives, different Bhojpuri native speakers were consulted and samples were collected and analyzed using different devices. Those consultants were selected randomly from different places and ages, both male and female. This empirical verification concludes that those sonorants are devoicing aspirate consonants, and word-stress is phonemic in Bhojpuri as English does have. This study is significant to explore such characters in other new Indo-Aryan languages if verified.